What do we know about the impact of stress on foster carers and contributing factors?. (December 2018) - Adams, Emma; Hassett, Alexander R; Lumsden, Virginia
Research has highlighted the many challenges that foster carers face in caring for children who have experienced adversity and has charted a growing mismatch between the numbers of children needing placements and the availability of carers. This review synthesises and evaluates the current empirical evidence on the causes and consequences of stress experienced by foster carers and the factors that lessen or increase it. PsychINFO, ASSIA, Web of Science and Google Scholar were searched for relevant studies, 15 of which met the specific inclusion criteria. The factors identified included both system variables, such as working in a wider service framework, and individual ones, such as children's behaviour. One consequence of this stress was reduced foster carer retention. Scrutiny of the papers also revealed methodological issues related to sampling, research design and cultural variability. Topics for future research were identified, especially an analysis of the perspectives of people involved in the system around foster carers, such as social workers and the carers' birth children. Clinical implications were also highlighted, most notably the promotion and provision of effective training and support and the development of integrated ways of working with services and foster carers' families.